The effect of health education programs for parents about breakfast on students' breakfast and their academic achievement in the north of Jordan - Kawafheh, Mariam M.; Hamdan, Falastine R.; Abozeid, Shalabia El-Sayed; Nawafleh, Hani (International Journal of Advanced Nursing Studies, 2014)
Background: Breakfast is often said to be the most important meal of the day, there is a significant evidence of positive academic effects due to breakfast consumption. Objectives: The purpose of this study is to examine whether the health education intervention about breakfast for parents leads to improvement in students' breakfast intake and their academic achievements, it also aims at investigating the effect of students' gender and class on their performance. Methods: The sample of the study was selected by random sampling technique. It consisted of (234) students, (115) male and (119) female students at Fatima Bent Al Yaman school for girls and Khaled Ben Al Walid school for boys in Irbid the first Directorate of Education in the first semester 2013/2014 and was distributed into four sections, which were selected purposefully two female sections and two male sections. Results: findings of the study indicated that there were statistically significant differences in the post- tests between the control and the experimental groups in favor of the experimental group which their parents were exposed to health education intervention about breakfast, and there was no statistically significant difference in the students' achievement due to gender or to the interaction between gender and group. Conclusion: breakfast has a positive effect on students’ academic performance. Keywords: Academic Achievement, Health Education Programs, School Children.